2018
DOI: 10.1002/celc.201800795
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Flower‐Like MoS2@Carbon Nanotube Composites with Interconnected Porous Networks and High Catalytic Activity as Cathode for Lithium‐Oxygen Batteries

Abstract: Lithium-oxygen (LiÀO 2 ) batteries show great potential to become one of the most promising energy-storage and conversion systems owing to their ultrahigh theoretical specific energy (~3505 Wh kg À1 ). However, commercialization of Li-O 2 batteries is constrained by a large charging overpotential caused by the sluggish electrode kinetics and low conductivity of the discharge product, resulting in unsatisfied energy efficiency and poor cyclability. In this paper, aiming to address these issues, we propose uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…[28] Long et al found that LiÀ O 2 battery catalyzed by MoS 2 /CNTs can be cycled for 141 cycles at 1000 mA h g À 1 . [26] These two results suggest that the sulfides can be the highly effective catalysts for LiÀ O 2 batteries. Moreover, some bismuth chalcogenides have been applied to several catalytic fields such as ORR, [29] OER, [30] hydrogen evolution reaction (HER) [31] and carbon dioxide conversion [32] due to the good catalytic abilities.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…[28] Long et al found that LiÀ O 2 battery catalyzed by MoS 2 /CNTs can be cycled for 141 cycles at 1000 mA h g À 1 . [26] These two results suggest that the sulfides can be the highly effective catalysts for LiÀ O 2 batteries. Moreover, some bismuth chalcogenides have been applied to several catalytic fields such as ORR, [29] OER, [30] hydrogen evolution reaction (HER) [31] and carbon dioxide conversion [32] due to the good catalytic abilities.…”
Section: Introductionmentioning
confidence: 94%
“…Long et al. found that Li−O 2 battery catalyzed by MoS 2 /CNTs can be cycled for 141 cycles at 1000 mA h g −1 . These two results suggest that the sulfides can be the highly effective catalysts for Li−O 2 batteries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 24 ] The dispersed 1D CNT can form 3D porous interconnected networks for fast electron transfer and abundant void volume, which aids in maintaining the cathode integrating during cycling, and thus superior rate capability and cyclic reversibility could be achieved. [ 24d,25 ] However, it is believed that carbon materials would react with electrolyte and even the discharge products under relatively high potentials, leading to the obvious battery performance decay with the continuous formation and accumulation of by‐products. [ 26 ] Hence, an effective protection strategy needs to be applied to refrain from the carbon material corrosion in LOBs.…”
Section: Introductionmentioning
confidence: 99%